Environmental drivers of phytoplankton with focus on potentially toxic cyanobacteria in a shallow lake used as drinking water source: Sauce Lake, Maldonado, Uruguay (INNOTEC, 2017)
Sauce Lake, the main drinking water source in Maldonado, Uruguay, has been registering recurring events of potentially toxic cyanobacterial blooms that affect its service. This leads to the necessity of exploring the environmental drivers in the composition of phytoplankton, particularly in the presence of potentially toxic cyanobacteria. In this study we analyzed the environmental factors associated with phytoplankton composition and biomass, particularly of cyanobacteria. We sampled physicochemical variables, nutrients and phytoplankton during the summer 2015-2016 with a weekly frequency, in six sites of Sauce Lake. The results show a very high temporal and spatial variability in the phytoplankton composition, with cyanobacterial algal blooms of different taxa: Dolichospermum crassum, Cuspidothrix issatschenkoi, Microcystis aeruginosa, Microcystis panniformis y Sphaerocavum brasiliense. We observed that turbidity is a key factor controlling the total phytoplankton biomass, while the NT vs. PO4 concentrations determined the differential presence of potentially toxic cyanobacteria. The analysis of the relationship between these nutrients could contribute to anticipate different cyanobacterial harmful algal blooms in this ecosystem, enabling the development of management tools oriented to decrease its negative effects, particularly in the purification process.
Keywords: Harmful Algal blooms; phytoplankton composition; biomonitoring; drinking water supply